Career and Career Guidance in the Nordic Countries - Haug, Erik Hagaseth; Hooley, Tristram; Kettunen, Jaana; Thomsen, Rie (Career Development Series, 2020)
Career and Career Guidance in the Nordic Countries explores what kind of context the Nordic region offers for the pursuit of career, how the development of careers are supported and how career guidance is enacted in this context.; Readership: All interested in career and career development, including students, researchers, practitioners and policy makers. There will also be important secondary audiences amongst scholars of wider education and employment practice, particularly in the Nordic countries.